As vulnerabilidades da agricultura familiar e as ameaças das lavouras de soja ao projeto de assentamento São Pedro, Amazônia, Brasil - Jôine Cariele Evangelista do Vale; Marla Weihs; Wagner Gervazio (Confins)
This work was developed in the São Pedro land reform settlement project, located in the municipality of Paranaíta, Brazilian Midwest. Our objective was to understand some of the vulnerabilities of family farming and the threats generated by the advance of soybean crops towards settlement. Data were collected through semi-structured interviews, participant observation and construction of timelines. The results indicate that, over time, the economic stabilization of families has always been temporary, having been affected by a historical lack of structure and adequate agricultural policies, which have hindered the continuity of agricultural activities. Thus, cattle ranching replaced grain crops in the early 2000s. The current expansion of large soybean-producing properties in the vicinity of the settlement exposes farmers to the threat of commercialization or leasing of land, especially in view of the degradation of pastures on many properties. In the current context, obtaining land title and access to agricultural credit are necessary elements for strengthening family farming in the settlement.